The Effect of Self-Confidence on Mental Toughness of Adolescent Pencak Silat Athletes - Naliza, Mifta; Wijayaningsih, Dian Estining; Hudaya, Abdillah Arju; Pebrian, Ryan; Firmansyah, Randy Adi; Alim, Abdul; Nurfadhila, Risti; Salafi, Muhammad Irvan Eva; Budiarti, Ratna (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
Self-confidence is one of the variables that impact the development of mental toughness. This study aimed to determine the relationship between mental toughness and self-confidence in adolescent pencak silat athletes. The quantitative description method was used in this study. This study used a purposive sampling technique for the sample. The study population amounted to one hundred and fifty athletes, with a sample of fifty teenage athletes who were members of the martial arts clubs Persaudaraan Setia Hati Terate, Merpati Putih, and Perisai Diri. The data acquisition method carried out during this period consisted of questionnaires and observations. The instruments used in this study were Pratama's self-confidence scale and Sella's mental toughness scale. The data analysis method used simple regression with SPSS. The findings of this study indicate that the self-confidence of adolescent pencak silat athletes is in the